2020
DOI: 10.3390/en13030601
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a High-Voltage Room Quasi-Smoke Gas Explosion

Abstract: During an air separation unit shut-down in a methanol production plant, a stop signal was sent to the control cabinet of a synchronous motor for a booster compressor. The control cabinet stopped magnetizing the rotor, while the system logic ensured that the power circuit breakers for the start reactor coils were opened, in order to be ready for the next start-up. Unintentionally, the circuit breaker was still connected (i.e., power was let through the reactors for a prolonged time period), which led to extensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…There has been much focus on preventing and mitigating fires in hydrocarbon-carrying pipes and equipment, and research on, e.g., active [28,29] and passive [30,31] fire protection of these systems. However, in recent years, several incidents in Norway have struck the utility systems, e.g., a high-voltage room quasi-smoke gas explosion [32] and a major fire in a steam-powered turbine generator [33] as well as the fire analyzed in the present study [4,5]. It may be concluded that the utility systems need more risk attention.…”
Section: Discussionmentioning
confidence: 87%
“…There has been much focus on preventing and mitigating fires in hydrocarbon-carrying pipes and equipment, and research on, e.g., active [28,29] and passive [30,31] fire protection of these systems. However, in recent years, several incidents in Norway have struck the utility systems, e.g., a high-voltage room quasi-smoke gas explosion [32] and a major fire in a steam-powered turbine generator [33] as well as the fire analyzed in the present study [4,5]. It may be concluded that the utility systems need more risk attention.…”
Section: Discussionmentioning
confidence: 87%
“…Substituting Equation (12) and Equation 13into Equation 22 (11). Figure 1 shows the quantity of inert gas agents as a function of k. The required inert gas quantity to obtain a design oxygen level per unit enclosure volume decreases with increasing values of k. Therefore, venting out the air-agent mixture not only removes the overpressure effect in an enclosure, it also lowers the mass requirement of inert gas agents.…”
Section: Required Quantity Of Inert Gas Agentsmentioning
confidence: 99%
“…Some research [9] has been carried out to investigate the application of inert gas agents in some typical buildings for disabled persons, elderly in nursing homes, and other citizens with reduced cognitive function, etc. Inert gas agents also have great potential as inhibitors of gas explosions by reducing or possibly eliminating the risk of explosions [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In a case study, UniCPS was implemented in a local factory for PdM demonstration. One of the significant parameters is RMS current (Irms), which needs to be closely monitored because fire, explosion, and injury cases are often reported [7] due to the electrical current faults. Therefore, real-time data visualization and anomaly detection is also demonstrated, particularly on electrical RMS current data.…”
Section: Introductionmentioning
confidence: 99%